Antibacterial Activity of Kecombrang Flower (Etlingera elatior (Jack) R.M. Sm) Extract against Staphylococcus epidermidis and Propionibacterium acnes - Vilya Syafriana; Renita Noviani Purba; Yayah Siti Djuhariah (Journal of Tropical Biodiversity and Biotechnology, 2021)
This study aimed to determine the antibacterial activity from the ethanol extract of Kecombrang flower (Etlingera elatior (Jack) R.M. Smith) against Staphylococcus epidermidis and Propionibacterium acnes. The extract was made by the maceration method with 70% ethanol as a solvent. Antibacterial activity test was carried out by the disk diffusion method with a concentration of 10%, 20%, 40%, and80%. Meanwhile, theMinimum InhibitoryConcentration(MIC)was done atconcentrations of 10%, 8%, 6%, 4%, and 2%. The results showed that the Kecombrang flower (Etlingera elatior (Jack) R.M.Smith) extract hadantibacterialactivityagainstS.epidermidisand P. acnes. The MIC for S. epidermidis is at a concentration of 4%, while in P.acnes cannot determine yet.